Agro-ecosystem modeling can aid in the optimization of biomass feedstock supply. (November 2016) - Dufossé, Karine; Drouet, Jean-Louis; Gabrielle, Benoît
Abstract: Recent European Directives promoted the development of biofuels, requesting mandatory limits to their emissions ot greenhouse gases (GHG). Second-generation biofuels based on lignocellulosic biomass are prime candidates but their GHG emissions are variable and uncertain. Agro-ecosystem modeling can capture them and the performance of biofuel feedstocks. This study aimed at optimizing feedstock supply for a bioethanol unit in France, from agricultural residues, annual and perennial crops. Their productivity and environmental impacts were modelled on a regional scale using geo-referenced data on soil properties, crop management, land-use and future weather data. Several supply scenarios were tested. Cereal straw was the most efficient feedstock but had a low availability, and only miscanthus could meet the bioethanol plant's demand. Sorghum combined poor yields and high GHG emissions compared by miscanthus and triticale. A mix of three biomass sources used less than 3% of the regional agricultural land while abating GHG emissions by 60%. Highlights: The production of biomass and its environmental impacts can be mapped with agro-ecosystem models. Variability in soil and climate conditions can be used to optimize biomass supply mixes. Appropriate selection of feedstocks mitigates the carbon-intensity of biofuels. Perennial crops and agricultural residues out-perform annual crops, but their availability is limited. Relying on multiple biomass feedstock sources is recommended.